Ablation of microRNAs in VIP+ interneurons impairs olfactory discrimination and decreases neural activity in the olfactory bulb. (12th January 2022) - Wu, Jing; Liu, Penglai; Mao, Xingfeng; Qiu, Fang; Gong, Ling; Wu, Jinyun; Wang, Dejuan; He, Miao; Li, Anan
Abstract: Aim: MicroRNAs (miRNAs) are abundantly expressed in vasoactive intestinal peptide expressing (VIP + ) interneurons and are indispensable for their functional maintenance and survival. Here, we blocked miRNA biogenesis in postmitotic VIP + interneurons in mice by selectively ablating Dicer, an enzyme essential for miRNA maturation, to study whether ablation of VIP + miRNA affects olfactory function and neural activity in olfactory centres such as the olfactory bulb, which contains a large number of VIP + interneurons. Methods: A go/no‐go odour discrimination task and a food‐seeking test were used to assess olfactory discrimination and olfactory detection. In vivo electrophysiological techniques were used to record single units and local field potentials. Results: Olfactory detection and olfactory discrimination behaviours were impaired in VIP + ‐specific Dicer‐knockout mice. In vivo electrophysiological recordings in awake, head‐fixed mice showed that both spontaneous and odour‐evoked firing rates were decreased in mitral/tufted cells in knockout mice. The power of ongoing and odour‐evoked beta local field potentials response of the olfactory bulb and anterior piriform cortex were dramatically decreased. Furthermore, the coherence of theta oscillations between the olfactory bulb and anterior piriform cortex was decreased. Importantly, Dicer knockout restricted to olfactory bulb VIP + interneurons recapitulated the behavioural and electrophysiological results of the global knockout. Conclusions: VIP + miRNAs are an important factor in sensory processing, affecting olfactory function and olfactory neural activity.